2019
DOI: 10.1590/0104-6632.20190363s20180361
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Viscoplastic Flow in a T-Bifurcation: Identification of Stagnant Regions

Abstract: Identification of stagnant regions of viscoplastic fluid flows in production lines and equipment is of paramount importance owing to potential material degradation and process contamination. The present work introduces an assessment strategy to identify, classify and quantify unyielded regions with the objective of optimizing the flow conditions with the purpose of minimizing stagnant regions. Flow of Carbopol ® 980 in a T-bifurcation channel is adopted to illustrate the procedure. The rheological behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The side view of the T‐junction along with the generated mesh is shown in Figure 1. The lengths of the main channel and the bifurcation arms are the same (0.3 m), and the width of each is 0.03 m. The dimensions of the T‐junction are taken from the work of Inácio et al [ 23 ] The coordinates of the BB′ section at the entrance of the bifurcation are (0.3, 0.04) and (0.33, 0.04) on the inner and outer arms, respectively. The coordinates of the symmetric CC′ section on the bottom arm of the bifurcation are (0.3, −0.01) and (0.33, −0.01) on the inner and outer arms, respectively.…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The side view of the T‐junction along with the generated mesh is shown in Figure 1. The lengths of the main channel and the bifurcation arms are the same (0.3 m), and the width of each is 0.03 m. The dimensions of the T‐junction are taken from the work of Inácio et al [ 23 ] The coordinates of the BB′ section at the entrance of the bifurcation are (0.3, 0.04) and (0.33, 0.04) on the inner and outer arms, respectively. The coordinates of the symmetric CC′ section on the bottom arm of the bifurcation are (0.3, −0.01) and (0.33, −0.01) on the inner and outer arms, respectively.…”
Section: Problem Formulationmentioning
confidence: 99%
“…They validated the CFD simulation (performed along with an evaporation–condensation model) against the experimental data obtained from the emergency core cooling apparatus: they found that the condensation rate was directly proportional to the thermodynamic ratio (Rt number). Inácio et al [ 23 ] investigated the flow behaviour of a Herschel–Bulkley model (regularized by Papanastasiou's approach) in a 2D T‐junction and showed the presence of stagnant zones at the root of the bifurcation; these decrease in extent as Re increases. Further, recirculation regions form near the root of the bifurcation at higher Re.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third benchmark case is a flow in two dimensional T-branch. For validation the numerical simulations performed by Inácio et al [26] are considered, performed using commercial software. The program uses the finite volume (FVM) to discretize the conservation equations based on a cell-centered formulation and a second order scheme for discretization of the viscous terms.…”
Section: Flow In a T-branchmentioning
confidence: 99%
“…The flow requires a long inlet section, therefore it is interesting for validating the streamwise velocity component in the channel as the first step. The comparison of the two profiles, one from [26] and present simulation, for the profile at same cross-section position, at x = 15H , where H is the height of the channel, is given in Fig. 3…”
Section: Flow In a T-branchmentioning
confidence: 99%